MEASUREMENT OF THE CERVICAL LENGTHIN 20-24 WEEKS GESTATION, HISTORY OF PREVIOUS PRETERM LABORAND ASSESSMENT OF THE VAGINAL MICROFLORA FOR BACTERIAL VAGINOSIS IN THE FIRST TRIMESTER AS A POPULATIONAL SCREENING FOR PRETERM BIRTH - Ivan D. Ivanov (Journal of IMAB, 2020)
Preterm delivery (PTD) is a problem with a social significance, considering the fact, that it is a leading cause for perinatal complications and perinatal mortality and spending resources in healthcare and those who are born pretermhave a high risk for complications, chronic disability. The rate of preterm birth has not decreased in the last 50 years and continues to grow, despite the advances of the medical science and the understanding of the risk factors and the mechanisms leading to preterm birth. It is considered that one of the main reasons for that is the absence of a standard, easily applicable and effective screening protocol in routine antenatal care. The objective of this study is to evaluate the ability of the combination of the history of prior preterm birth, cervical length measurement in 20-24wg and the assessment of the vaginal microflora in the first trimester as a screening for spontaneous PTD. This was an observational and prospective study of 334 unselected pregnant women and data were collected about risk factors, such as the history of previous PTD, conception method (spontaneous or after ART),etc. to estimate the prevalence and the significance of these factors and to define an algorithm to estimate the individual risk of PTD. The combination of the history of prior PTD and second trimester cervical length measurement allows estimation of the risk for PTD. The proposed screening is applicable in the routine practice, doesn’t require additional resources, and it could be expected that its introduction would lead to lowering of the burden of PTD (neonatal morbidity, mortality, etc.).